Outcome of Tumor Lysis Syndrome with Hydration and Alkalinization in Children with Acute Lymphoblastic Leukemia - Sultana, Armin; Islam, Afiqul; Akhtar, Gulshan; Rahman, Md Abdur (Bangladesh Journal of Medical Science, 2012)
Objective: To observe the out come of tumor lysis syndrome (TLS) following treatment with hydration and alkalinization in children with acute lymphoblastic leukemia. Methodology: This is an observational study which included 30 diagnosed ALL children who were at high risk of developing TLS in the Department of Pediatric Hematology & Oncology, BSMMU, from January 2010 to July 2010. Result: The mean (±SD) age was found 10.2±2.9 years and maximum (46.7%) numbers were found between 11 to 15 years. Male female ratio was 2.3:1. High risk patients for developing TLS presented with huge organomegaly such as hepatomegaly, splenomegaly, and lymphadenopathy associated with fever, anemia, and bony tenderness. For diagnosis of Acute Lymphoblastic Leukemia (ALL) bone marrow study was done in all patients and immunophenotyping in 40.0% patients. Hydration, Alkalinization, Tab Allopurinol and Oral Aluminum hydroxide were used in all study patients while treatment. WBC and serum uric acid were found higher in all patients during baseline investigation. After hydration and Alkalinization serum potassium, serum phosphate, serum calcium and serum creatinine level were normal within 72 hours and serum uric acid within day five. Mortality was found 6.7% and the cause of mortality was septicemia. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12598 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12